Geographic measures of retail food outlets and perceived availability of healthy foods in neighbourhoods. Issue 8 (2nd October 2015) - Barnes, Timothy L; Freedman, Darcy A; Bell, Bethany A; Colabianchi, Natalie; Liese, Angela D
Abstract: Objective: To examine associations between geographic measures of retail food outlets and perceived availability of healthy foods. Design: Cross-sectional. Setting: A predominantly rural, eight-county region of South Carolina, USA. Subjects: Data from 705 household shoppers were analysed using ordinary least-squares regression to examine relationships between geographic measures (presence and distance) of food outlets obtained via a geographic information system and perceived availability of healthy foods (fresh fruits and vegetables and low-fat foods). Results: The presence of a supermarket within an 8·05 km (5-mile) buffer area was significantly associated with perceived availability of healthy foods ( β =1·09, P =0·025) when controlling for all other food outlet types. However, no other derived geographic presence measures were significant predictors of perceived availability of healthy foods. Distances to the nearest supermarket ( β =−0·16, P =0·003), dollar and variety store ( β =−0·15, P =0·005) and fast-food restaurant ( β =0·11, P =0·015) were all significantly associated with perceptions of healthy food availability. Conclusions: Our results suggest that distance to food outlets is a significant predictor of healthy food perceptions, although presence is sensitive to boundary size. Our study contributes to the understanding and improvement of techniques that characterize individuals' food options in their community.